Relationship of Organizational Culture with The Implementation of Good Hospital Governance (GHG) at Bhayangkara Hospital Makassar - Dian Ekawaty; Sriyani Windarti; Nurmulia Wunaini Ngkolu; Nining Ade Ningsih; Reza Nur (Universitas Mandala Waluya, 2023)
The results of the initial interview revealed that Bhayangkara Hospital Makassar adheres to a hierarchical system with a management system based on the leadership command line. Management in implementing an organizational culture where the Bhayangkara Hospital Makassar consisting of members of the police, ASN and BLU adheres to the applied police values. This study aims to determine the relationship between organizational culture and the implementation (GHG) of good hospital governance in Bhayangkara Hospital Makassar. This type of research used descriptive quantitative research with a Cross-Sectional Study approach. The population in this study were all employees at the Bhayangkara Hospital Makassar as many as 207 people the sampling technique used the Slovin formula so that a sample of 136 respondents was obtained and the data analysis technique used Multiple Linear Regression Tests with SPSS assistance. The results of this study indicate an assessment of variables the values obtained are sig.= 0.031 < 0.05. Confidence variable obtained a sig. value of 0.045 < 0.05. Organizational climate variable is obtained sig.= 0.026 < 0.05. The tradition variable was obtained with a value of sig.= 0.020 <0.05. The conclusion in this study is that the variables of belief, organizational climate and tradition have a significant relationship to Good Hospital Governance in Bhayangkara Hospital Makassar.